Heme cavity dynamics of photodissociated CO from ba3-Cytochrome c oxidase : the role of ring-D propionate - Porrini, Massimiliano; Daskalakis, Vangelis; Farantos, Stavros C.; Varotsis, Constantinos (My University, 2009)
Intracavity molecular dynamics studies of photodissociated carbon monoxide from ba3-cytochrome c oxidase have been performed by sampling the phase space with several hundreds of trajectories each integrated up to 100 ps time interval. It is shown that the cis conformation of protonated ring-D propionate of heme a3 and its trans conformation for the deprotonated species control the CO location by creating two distinct equilibrium states for CO confined in a cavity internal to the distal heme pocket. Thus, these cis (closed gate) and trans (open gate) conformations of heme a3 propionate D play the role of a switch, opening or closing a gate for confining CO in a cavity internal to the heme pocket or releasing it to a bigger outer cavity. The geometry of the inner cavity and the validity of the potential function employed are further investigated by Density Functional Theory calculations for the active site, potential of mean force curves along the copper-CO bond, as well as with Quantum Mechanics/Molecular Mechanics calculations. In the light of the present study, trajectory scenarios for the dissociation of CO previously suggested from time-resolved infrared spectroscopy are re-examined
Keywords: Porphyrins; Carbon monoxide; Density functionals; Hemoglobin; Infrared spectroscopy; Molecular dynamics; Spectroscopic analysis; Copper; Heme; Chemistry